2020
DOI: 10.1038/s41467-020-16411-5
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 disrupts mitochondrial transport and causes axonal degeneration via a CaMKII-dependent elevation of intracellular Ca2+

Abstract: The cation channel transient receptor potential vanilloid 4 (TRPV4) is one of the few identified ion channels that can directly cause inherited neurodegeneration syndromes, but the molecular mechanisms are unknown. Here, we show that in vivo expression of a neuropathy-causing TRPV4 mutant (TRPV4R269C) causes dose-dependent neuronal dysfunction and axonal degeneration, which are rescued by genetic or pharmacological blockade of TRPV4 channel activity. TRPV4R269C triggers increased intracellular Ca2+ through a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 68 publications
1
35
0
Order By: Relevance
“…TRPV4 channels are composed of four TRPV4 subunits that assemble into homotetramers 12 . Given that TRPV4 neuropathy mutations cause autosomal dominant disease and cause a gain of function in vivo 26 , we hypothesized that the co-expression of mutant TRPV4 might disrupt the normal binding of WT TRPV4 with RhoA. We first tagged WT and neuropathy mutant TRPV4 with different epitope tags and used co-immunoprecipitation to confirm that WT and mutant TRPV4 were able to associate in cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPV4 channels are composed of four TRPV4 subunits that assemble into homotetramers 12 . Given that TRPV4 neuropathy mutations cause autosomal dominant disease and cause a gain of function in vivo 26 , we hypothesized that the co-expression of mutant TRPV4 might disrupt the normal binding of WT TRPV4 with RhoA. We first tagged WT and neuropathy mutant TRPV4 with different epitope tags and used co-immunoprecipitation to confirm that WT and mutant TRPV4 were able to associate in cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of TRPV4 disease mutants in heterologous systems have demonstrated that both neuropathy and skeletal dysplasia mutations lead to gain of ion channel function, increased basal and stimulated TRPV4-mediated calcium influx, and cytotoxicity that can be rescued with channel antagonists 1 , 2 , 7 , 16 , 24 , 25 . Furthermore, neuronal degenerative phenotypes in a fly model of TRPV4 neuropathy are suppressed by either an inactivating mutation within the ion channel pore or treatment with a TRPV4 channel antagonist 26 . However, increased ion channel activity cannot solely account for the tissue-selective pathology caused by TRPV4 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…For another, Miro has two EF calcium binding domains and Miro will directly bind KIF5 when binding of calcium (Liu and Hajnóczky, 2009 ), which will prevent motor activity. Therefore, increased intracellular calcium levels are sufficient to inhibit this process (Woolums et al, 2020 ).…”
Section: Normal Mitochondrial Behavior In Axonsmentioning
confidence: 99%
“…This is supported by its localization in paranodal regions of rat Schwann cells, where its proximity to another CMT gene product, gap junction protein beta‐1 (GJB1), may allow swift propagation of Ca 2+ signals from cell to cell 27 . Abnormal Ca 2+ flux could contribute to altered axonal Ca 2+ microdomains that disturb mitochondrial transport, as has been suggested for dominant mutations in the plasma membrane cation channel transient receptor potential cation channel, subfamily V, member 4 (TRPV4) 28‐31 which cause CMT2C 32‐34 . Furthermore, mutations in other components of the IP 3 signaling pathway, for example, FIG4 and SBF2 , cause demyelinating CMT, 35‐36 which highlights the importance of this pathway for peripheral myelin maintenance.…”
Section: Discussionmentioning
confidence: 94%